(untitled) (Clinics, 2023)
Background: Lung transplantation represents the definite treatment for CF patients with advanced-stage pulmonary disease. Recent major developments in the treatment of CF indicate the need for an evaluation of lung transplantation as the current best practice in end-stage disease. This systematic review was performed to evaluate the impact of lung transplantation on health-related quality of life in patients with CF. Methods: PubMed was searched for studies matching the eligibility criteria between January 2000 and January 2022. OVID (MEDLINE), Google Scholar, and EBSCOhost (EMBASE) as well as bibliographies of included studies were also reviewed. Applying predetermined eligibility criteria, the included studies were selected. Predetermined forms were used to conduct a quality appraisal and implement data tabulation. Results were synthesized by narrative review. This systematic review was prospectively registered in the PROSPERO register (CRD 42022341942). Results: Ten studies (1494 patients) were included. Lung transplantation results in improvements in HRQoL in CF patients relative to their baseline waitlisted state. Up to five years postoperatively CF patients retain their HRQoL at levels similar to the general population. There are several modulating factors that impact HRQoL outcomes in CF patients post-LTx. Compared to lung recipients with other diagnoses CF patients achieve either greater or equal levels of HRQoL. Conclusion: Lung transplantation conveys improved HRQoL to CF patients with the advanced-stage pulmonary disease for up to five years, and to levels comparable to the general population and non-waitlisted CF patients. This systematic review quantifies, using current evidence, the improvements in HRQoL gained by CF patients following lung transplantation.